Temperature inversion and thermal belt in the Slovenske gorice region between the Mura and Pesnica Rivers - Marič , Martin (Journal for Geography, 2016)
Temperature inversion and thermal belt are the two topoclimatic phenomena, which influence the prevelance of vineyards and orchards in the Slovenske gorice region. The presence of temperature inversion and thermal belt within the Slovenske gorice region was proven by our measurements and analyses. Furthermore, we analysed their occurrence and their intensity in different weather types. Our aim was also to prove the lower limit of thermal belt in the Slovenske gorice region between the Mura and Pesnica Rivers.
Keywords: temperature inversion; thermal belt; weather type; the Slovenske gorice region between the Mura and Pesnica Rivers